Leveraging Trends in Neurology Admissions for Departmental Planning During the COVID-19 Pandemic. (April 2021) - Lau, K. H. Vincent; Anand, Pria; Greer, David M.; Cervantes-Arslanian, Anna; Phicil, Sheila; Moore, Jesse; Takahashi, Courtney
The COVID-19 pandemic has led to shifts in healthcare utilization for patients both with and without COVID-19. We aimed to determine how trends in neurology service admissions during the pandemic may aid in departmental planning by predicting future clinician staffing and other needs. We examined all admissions to the general neurology, stroke, and neurocritical care services from January 31 to May 16, 2020 at our tertiary-care hospital using an electronic health record query, comparing these to analogous data in 2019. We trended admission rates and projected future censuses using logarithmic regression, tracked changes in length of stay (LOS), and quantified shifts in presentations of specific diagnoses. Daily rates of admissions declined sharply during the week of March 13, 2020 (the week after pandemic status was declared by the World Health Organization). On the censoring date, we projected a return to pre-pandemic censuses in the week of June 21 and used this information to make decisions regarding neurology resident schedules. There was a trend toward increased LOS for general neurology and stroke patients between March 27 and April 9, 2020 compared to in 2019, with subsequent decline coinciding with early hospital initiatives. Since March 13, 2020, there has been a trend toward reduced presentations of ischemic stroke, suggesting a need for community education on stroke awareness. Characterizing early trends in neurology admissions may allow physician administrators to plan local and community-level responses to the pandemic.